A comparative study of 5-level and 7-level multilevel inverter connected to the grid - Yusof, N.A.; Sapari, N.M.; Mokhlis, Hazlie; Selvaraj, J. (2012)
Power electronic converters were developed for integrating the photovoltaic (PV) arrays and utility grid. Inverters are needed to convert the direct current electricity produced by the PV array into alternating current electricity required for loads. Nowadays, multilevel inverter gained so much popularity in PV systems. Multilevel inverter promises a lot of advantages over conventional inverter especially for high power applications. Some of the advantages are that the output waveform were improved since multilevel inverter produced nearly sinusoidal output voltage waveforms, hence the total harmonic distortion also low. The switching losses also become less. And, the filter needed to smooth the output voltage is small; hence, the system is compact, lighter and much cheaper.